An Analysis of News Construction in Online Media (Green Publisher, 2026)
This study aims to analyze the news construction of the Constitutional Court's (MK) ruling on the acid attack against Novel Baswedan–a senior KPK investigator–perpetrated by unknown individuals, on Detik.com. The analysis was conducted using Robert N. Entman’s model, focusing on four dimensions: defining problems, diagnosing causes, making moral judgments, and treatment recommendations. This study employs a qualitative method within a constructivism paradigm. Data collection was conducted through the observation of news coverage on Detik.com regarding the trial proceedings of the perpetrators of the acid attack on Novel Baswedan. Out of the numerous news reports, four articles were selected as representative to portray the trial process and the judge's verdict on the perpetrators The results demonstrate that Entman views framing in two major dimensions: issue selection and the emphasis or salience of specific aspects of reality and issues. Furthermore, the analysis reveals that Detik.com's news framing sided with Novel Baswedan, as evidenced by the news content which was predominantly presented from the perspective of Novel Baswedan's defenders.